Qualitative Study of the Feasibility of HPV Vaccine Delivery to Young Adolescent Girls in Vietnam : Evidence from a Government-Implemented Demonstration Program - LaMontagne, D. Scott; Nghi, Nguyen Quy; Nga, Le Thi; Janmohamed, Amynah; Huyen, Dang Thi Thanh; Hien, Nguyen Tran; Davis Tsu, Vivien (BioMed Central, 2015)
Introduction of human papillomavirus (HPV) vaccine in national programs has proceeded apace since 2006, mostly in high-income countries. Recently concluded pilots of HPV vaccination in low-income countries have provided important lessons learned for these settings; however, rigorous evaluations of the feasibility of these delivery strategies that effectively reach young adolescents have been few. This paper presents results from a qualitative evaluation of a demonstration program which implemented school-based and health center–based HPV vaccinations to all girls in grade 6, or 11 years of age, for two years in four districts of Vietnam.